Adaptive PID controller design guidelines for a class of non-linear systems. (1st January 2014) - Nikranjbar, Abolfath
In this paper, the systematic model reference adaptive PID (APID) controller design for a class of uncertain non-linear systems is discussed. The exact linear system based upon feedback linearisation approach is employed to establish the equivalent linear model of the process, which is then employed to develop the controller. In order to demonstrate the performance of the proposed technique, the trajectory tracking of the single arm robot manipulator subjected to process uncertainties and input disturbance is conducted. Simulation results illustrate the superior performance of the APID algorithm achieving the targets by fully eliminating the severe load disturbance exerted to the robot consuming feasible amount of control energy. This remarkable performance proposes it as an effective robust control strategy in online and/or offline precise servo control applications.